The DECOMPOSITION RATE OF MANGROVE FOREST LITTER IN NAGARI PILUBANG, SUNGAI LIMAU SUB DISTRICT PADANG PARIAMAN DISTRICT : - - putri, irma leilani eka (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Mangrove forests are very important coastal ecosystems worldwide as they provide a wide range of ecological, economic, and social benefits. One of the key components of mangrove forest ecosystems is mangrove litter, which consists of leaves, twigs, and small organisms that fall from mangrove trees. This litter is a food source for decomposing organisms, such as crabs and mollusks, and contributes to the nutrient cycle of the mangrove ecosystem after going through the decomposition rate process. This study aims to determine the decomposition rate of mangrove litter in Nagari Pilubang, Sungai Limau District, Padang Pariaman Regency. This research was conducted in September 2023-January 2023. This research method uses a litter bag to store leaf litter for 30 days and collection is done every 10 days with 3 collections and then the rate of decomposition is calculated. The results showed that on the last day the decomposition rate at station 3 was 0.365% which was higher than stations 1 and 2 which were only 0.418% and 0.412% respectively.